E-cigarette promotes breast carcinoma progression and lung metastasis: Macrophage-tumor cells crosstalk and the role of CCL5 and VCAM-1. (28th October 2020) - Pham, Kien; Huynh, Do; Le, Le; Delitto, Daniel; Yang, Lei; Huang, Jing; Kang, Yibin; Steinberg, Michael B.; Li, Jieliang; Zhang, Lanjing; Liu, Dongfang; Tang, Moon-Shong; et al.
Abstract: Young women represent a target of E-cigarette (E-cig) companies, raising concern for potential connections with breast cancer (BC) that have not yet been elucidated. We hypothesized that E-cig promotes BC development and lung metastasis possibly through BC-monocyte/tumor-associated macrophage (TAM) crosstalk via CCL5 and V-CAM-1 axes. We demonstrated that E-cig promoted the infiltration of circulating monocytes in mammary fat pad (MFP) model. Furthermore, E-cig exposure significantly enhanced BC cell growth in MFP tumor and metastatic lung colonization; immunohistochemical stains illustrated the increase of TAMs infiltration, reduced BC cell apoptosis and increased proliferation index after E-cig exposure. In vitro studies show E-cig vapor condensate (EVC) treatment upregulated protein expressions of CCL5, V-CAM-1, and other pro-tumorigenic factors in BC cells. Mechanistically, co-culture system demonstrated both EVC and macrophages independently stimulated BC cell growth and the migration via CCL5/CCR1/CCR5 axis. During metastasis, E-Cig exposure stimulated BC cell survival via direct interaction with infiltrated macrophages, regulated by VCAM-1 and integrin α4 β1. Our findings, for the first time, showed that E-cig promotes BC growth and metastasis. This study highlights the critical role of TAMs via CCL5 and VCAM-1 pathways in E-cig promoted BC tumor development. Highlights: E-cig promoted primary breast cancer (BC) and lung metastasis is facilitated by BC cells and monocytes/macrophages crosstalk. The number of tumor-associated macrophages significantly increases in primary and lung metastatic sites after E-cig exposure. E-cig stimulates tumor growth and monocyte/macrophage infiltration possibly through CCL5/CCR1/CCR5 signaling axis. The E-cig enhanced direct binding to monocytes protects BC cells from apoptosis via VCAM-1 pathway. This study provides the first robust scientific evidence to raise awareness regarding the risks of vaping.